Penyelesaian Sengketa Jasa Konstruksi Melalui Jalur Non-Litigasi - Ummah, Maela Khoirul; Afriansyah Tanjung; Moh. Lubsi Tuqo Romadhan (Universitas Muhammadiyah Kotabumi, 2025)
This study examines the mechanisms for resolving construction service disputes through non-litigation channels as an alternative to court proceedings. The focus of the study is on out-of-court settlements that offer a voluntary, informal, cost-effective, and time-efficient approach, making them the preferred choice for disputing parties. The research questions include: first, what are the mechanisms and procedures for resolving construction service disputes through non-litigation channels; second, what are the comparative advantages of non-litigation dispute resolution compared to the court process. This study uses a normative juridical method, relying on secondary data as the primary source, analyzed descriptively and analytically through an approach based on relevant laws and regulations in the construction services sector. The results of the study show that non-litigation channels are highly preferred among construction industry players due to the significant advantages they offer. These advantages include: a fast and efficient resolution process that does not hinder construction projects; confidentiality guarantees that protect the parties' reputations; the appointment of mediators or arbitrators with integrity and technical expertise in construction; as well as the potential to achieve a win-win solution that maintains long-term business relationships among the parties. These findings confirm that non-litigation mechanisms such as negotiation, mediation, conciliation, and arbitration provide practical added value in resolving construction disputes compared to conventional litigation processes, which tend to be time-consuming, costly, and adversarial.